Real-world glycemic outcomes of a tubeless automated insulin delivery system: a single-center observational study in Italy - Angelino, Silvia; Maiorino, Maria Ida; Petrizzo, Michela; Di Martino, Nicole; Caruso, Paola; Carbone, Carla; Pontillo, Alessandro; Maio, Antonietta; Longo, Miriam; Scappaticcio, Lorenzo; Bellastella, Giuseppe; Esposito, Katherine (Frontiers in Endocrinology, 2025)
BackgroundThe objective of this study is to describe the short-term change observed in CGM-related measures and relevant clinical variables in individuals with type 1 diabetes transitioning to Omnipod 5 insulin treatment within a real-world setting.MethodsThe study involved adults with type 1 diabetes treated with Omnipod 5, whose data were collected over a 14-days observation period prior to (Time 0) and following the (Time 1) initiation of the patch pump use.ResultsA total of 20 adults with well-controlled glycemia were included in the study. From baseline to follow-up, Time in Range (TIR) significantly increased from 57.3% to 67.3% (P<0.001). Concurrently, there were significant decreases in Time Above Range (TAR) Level 1 (mean difference, -4.7 ± 6.1%, P = 0.003) and Level 2 (-4.2 ± 6.1%, P = 0.018), as well as in Time Below Range (TBR) Level 1 (-1.0 ± 1.1%, P<001), TBR Level 2 (-0.4 ± 0.5%, P = 0.015), and Glycemia Risk Index (-13.8 ± 15.1 P<0.001). Importantly, no significant changes in insulin doses were observed during the study period.ConclusionsOmnipod 5 initiation allowed participants to improve CGM-related metrics and the quality of glucose control in the short-term, without increasing the need for insulin.